Propuesta de un sistema de mobiliario versátil para el espacio social en departamentos de tamaño reducido - Yépez Gaete, Nicolás (2020)
With the passage of time there has been a trend within the sector of the real estate housing projects towards the reduction of living spaces. In this sense, the market of Quito has been involved in a growing offer of apartments with averages below 80 square meters of housing, these projects focus mostly on young professionals. This is when, in theory, the furniture market should also adapt to these spaces, but the fact is that not too innovative solutions are still offer to those in this market segment. On the other hand, there are imported offers that are expensive and often do not enter the budget of this sector. Precisely here is where the Yellow Box sofa proposal is born. Furniture that gives the user a range of variations or options from which they can choose according to their needs, likes and available space. Its modular characteristics helps the design adapt to different spaces and enrich them through its different configurations. In addition, it maximizes its functionality, occupying spaces understood as dead spaces in common sofas. Likewise, and responding to the needs that have been appearing, and are projected to continue, it ensures a comfortable space to work from home. And also, taking advantage of the comfort and functionality of the hybrid module between a side table, a footrest and one more space for a person if the user has a guest.